BIBLIOGRAPHY TRIAL ON BASHKIR HISTORY, LANGUAGE AND LITERATURE IN TURKEY - Tülay Karakaya (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2017)
In this project, in Turkey Bashkir Turkish, works to do about its history and literature are scanned. The working consist of four parts. Introduction, bibliography, conclusion and table. In introduction part short information is given about Bashkir Turks’ history, geography which they lived and Bashkir Turkish. In bibliography part, there are seven main topics: published books about Bashkir Turkish, history and literature in Turkey parts from the book, parts essays, declarations, post gradute and doctorate thesis which are worked about Bashkir Turkish in Turkey. Besides, these main topics are ranged in the form of bottom booms as works which are done researchs about Bashkir Turkish, history and literature. Lastly conclusion in part, general assessment is to do about the workings and numbers of works to do last are summarized on the table.